EDUCATIONAL INFLUENCE OF THE TV COMMERCIAL - KNYCH, Aleksandra (Trends in education, 2012)
The main aim of the TV commercial is to arouse a desire for owning an advertised item. Apart from that the TV commercial mould certain attitudes among children and teenagers. Research shows that TV commercial influences moulding of consumerist attitude among children. Values present in commercials are mainly egoistic and hedonistic values.
Keywords: education; commercial; TV commercial; educational influence of TV commercial.